Developing the Arabic Language Teaching Unit Based on the Differentiated Learning Curriculum - Atiyatul Wafiroh, Siti; Al-Khatib, Hayat (Tadris Al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The Arabic language affiliation modules prepared by the teacher are an effective means of effective and efficient but meaningful learning. Away from the teaching module, which is part of the independent detailed model, to develop abilities that include four language skills, namely listening, speaking, reading, watching, as well as writing and presentation. Specialized modules that are not specialized in facilitating and meeting the requirements of diverse students in learning files and are ready for self-learning learning. Outstanding learning is a series of continuous teacher-oriented orientation that is geared towards student fundamentals as is greater in the teaching unit. Arabic teachers in educational schools are still struggling to create Arabic language teaching modules that adapt to standalone application and are still learning advanced skills from experiential and productive content. Therefore, it is necessary to develop Arabic language teaching modules based on a university approach to differentiated learning that is able to meet the basic requirements of students. The aim of this research is to develop the unit of teaching Arabic language in independent models. MTS Al-Guami, where lawyer units are supplied, has begun to implement an independent curriculum. The model of the research methodology used in this research is Model 4 which goes through four stages which are the development of harmful bacteria and the dissemination. The results of this research state that: Arabic language teaching modules are a river on technology Differentiated learning can meet the basic needs of students and is suitable for use as pedagogical aids in learning Arabic; experienced subjects are rated as super implementable; expert assessment results are rated as exceptionally feasible; interactive assessment results by students are rated as highly implemented; the impact of teaching on meeting students’ needs is rated as super modular Implementation.